Modelling and investigation of amoxicillin chemical interaction with mineral waters containing a significant amount of calcium and magnesium salts - Anna O. Dobrova; Olga S. Golovchenko; Victoriya A. Georgiyants (Pensoft Publishers, 2021)
In recent years, the interaction of drugs with the components of food and drinks has been actively researched to ensure rational therapy. It is particularly important for amoxicillin as an antibiotic group of drugs, considering the issue of resistance. A study of the interaction of amoxicillin with mineral waters, which in significant quantities may contain cations and anions and enter complexation reactions, has not been conducted before. For the study, various chemical and physicochemical methods were used. Also in vitro dissolution test with conditions of simultaneous administration of amoxicillin with mineral waters in a 0.1M HCl was modelled. Results showed that amoxicillin could form multiple complex compounds with magnesium cations in the 0.1 M HCl with different stoichiometry. The study showed that from several investigated mineral waters, presented on the Ukrainian market, the "Karpatska dzherelna" could interact with amoxicillin in the medium of a 0.1 M HCl.